Adjuvant therapies of acne: review of literatures - Randy Satria Nugraha Rusdy; Lili Legiawati; Irma Bernadette Simbolon Sitohang; Sondang Marisi Holong Aemilia Pandjaitan Sirait (Bali Dermatology Venereology and Aesthetic Journal, 2022)
Acne is a chronic inflammatory disorder affecting pilosebaceous unit with various clinical manifestation from comedone, papule, pustule, to nodule and cyst. Choice of treatment is based on acne severity. Prolong antibiotic use along with restriction of isotretinoin use in Indonesia can be a challenge in managing acne. A lot of treatment options from topical agent, systemic medication, comedone extraction, intralesional corticosteroid injection, chemical peeling, light and laser-based therapy, as well as diet modification can be used as an adjuvant to improve acne. Review of literatures was performed to present recent evidence toward the effectivity of adjuvant therapy as a part of acne management.